RON Expression Mediates Lipopolysaccharide-Mediated Dendritic Cell Maturation via March-I - Huang, Lingtong; Fang, Xueling; Zhang, Xuan; Wu, Weifang; Yao, Hangping; Fang, Qiang (Frontiers in Cellular and Infection Microbiology, 2021)
The macrophage stimulating protein (MSP)-Recepteur d'origine nantais (RON) signaling pathway regulates macrophage function. Here, we verified RON receptor expression in bone marrow-derived dendritic cells (BMDCs) by RT-PCR, Western blot, and flow cytometry. Flow cytometry was used to detect the changes in MHC II and CD86 expression following the inhibition of RON in BMDCs and splenic dendritic cells. Immunoprecipitation and Western blot were used to detect the level of MHC II and CD86 ubiquitination. An ELISA was used to detect cytokine release and a mixed lymphocyte reaction was performed to evaluate dendritic cell maturity. The results show that the inhibition of RON leads to an increase in the March-1 transcription, which intensifies the ubiquitination of MHC II and CD86, and ultimately leads to decreased expression of these two molecules. The mixed lymphocyte reaction provided evidence that RON inhibition decreased the ability of DCs to promote the proliferation of T cells. The MSP-RON signaling pathway may play an important role in LPS-stimulated DC maturation through March-I and may protect DC differentiation following LPS stimulation.